INFLUENCE OF RIPENING AGENTS ON THE PHYSICOCHEMICAL QUALITIES OF STORED ORANGES IN SOUTH EAST NIGERIA - PAUL T; SUNMOLA A T; OKOSA I; UMUNNA M F (Innovare Journal of Agricultural Sciences, 2025)
The objective of this study is to evaluate the influence of ripening agents on the physicochemical qualities of stored oranges. The different ripening agents, such as calcium carbide and tomatoes (ethylene-producing fruits) with different packaging materials (sack, polythene, and envelope) were introduced to the orange samples. The study employs analytical techniques and tools to assess the effects of ripening agents and packaging materials on the orange samples. The overall observation on the ripening agents was that both the organic and inorganic agents had good results and better oranges than the control sample. However, the results showed that organic ripening agents with sac as the packaging material had the best outcome. Hence, recommended to be used for the ripening of oranges.